Design and analysis of a composite fuselage. - Marco Aurélio Rossi (2008)
This study presents a new methodology developed for an analytical model of a composite fuselage. It presents also finite element analyses of the same composite fuselage and the results comparison of both studies. This comparison shows that the results of both studies present very good correlation for the least weight combinations of composite stacking sequence and prove the applicability of the analytical model methodology. Still using finite element analyses, the study also presents a weight comparison between a composite fuselage and an aluminum alloy fuselage. This comparison shows the weight reduction which the fuselage achieves through the use of composite materials.